Pengaruh Lingkungan Kerja, Kompensasi, Dan Stres Kerja Terhadap Kinerja Karyawan - Soegihartono Soegihartono (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Entering the development of the world of work which continues to advance rapidly along with technological developments which consistently progress rapidly. Human Resources (HR) are very important in maintaining the survival of a company. Companies are required to be able to maintain the quality of performance of their human resources, therefore companies are required to be able to evaluate the performance of their resources. This research aims to examine, analyze and explain the influence of the work environment, compensation and work stress on employee performance simultaneously and partially, as well as finding out which independent variables have a dominant influence on the dependent variable. The sample in this research were employees at PT. Seidensticker Indonesia. The research method used in this research is a quantitative research method using a sample of 100 respondents. Sampling used nonprobability sampling with purposive sampling technique. The data analysis method used in this research is descriptive analysis method and multiple linear regression analysis. The results of the research show that simultaneously the Work Environment, Compensation and Work Stress affect employee performance. This is shown by the results of multiple linear analysis Y = 0.485 X1 + 0.332 X2 + 0.198 X3 + e. Hypothesis testing shows the results of the t significance test, the Work Environment variable has the most significant influence on employee performance. The results of the coefficient of determination test (adjusted r square) show a value of 0.802, which means that the research variables are able to influence employee performance by 80.2%.